1978
DOI: 10.1093/bja/50.11.1125
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Disposition of Morphine After I.M. Administration in Surgical Patients

Abstract: The disposition of morphine when administered by i.m. injection was studied in 36 patients receiving morphine as part of premedication before general anaesthesia, and in five patients who received morphine as a postoperative analgesic after median sternotomy for coronary artery surgery (PCA group). Maximum plasma concentration of morphine (CP max) was 75.3 +/- 6.0 (mean elimination rate constant (k) 4.85 X 10(-3) min-1 and half-life (T1/2) = 143 min for the preanaesthetic group. The corresponding values for PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…morphine in animals has not been extensively studied. The time to peak effect in our cats was comparable with that reported in the dog and in humans (Rigg et al ., 1978; Stanski et al ., 1978; Fisher et al ., 1987; Kentala et al ., 1998; Barnhart et al . 2000).…”
Section: Discussionsupporting
confidence: 91%
“…morphine in animals has not been extensively studied. The time to peak effect in our cats was comparable with that reported in the dog and in humans (Rigg et al ., 1978; Stanski et al ., 1978; Fisher et al ., 1987; Kentala et al ., 1998; Barnhart et al . 2000).…”
Section: Discussionsupporting
confidence: 91%
“…However, there was a markedly greater delay with morphine and relatively less delay with nalbuphine. This cannot be attributed to differences in pharmacokinetics: the elimination half-life of morphine in females is 110 min (Rigg et al, 1978) and about 300 min for nalbuphine (Errick and Heel, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…This time-honoured method has little rational basis when drug effect is considered in relation to the pharmacokinetics of the disposition of drugs such as meperidine TM and morphine. 75 These studies showed that a standard intramuscular dose of these agents in surgical patients resulted in a wide spectrum of plasma concentration profiles and clinical effects. The threshold concentration for analgesia has been estimated to be 50 ng/ml for morphine TM and 680 ng/ml for meperidine, 77 although in both instances these estimations are crude and open to considerable doubt.…”
Section: Analgesiamentioning
confidence: 99%